2004
DOI: 10.1159/000073980
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Primary Brain Tumor Diagnoses and Codes in Cancer Surveillance Systems

Abstract: High-quality cancer registry data are essential for assessing trends in incidence rates. This study evaluated the consistency of brain tumor surveillance data using a random sample of cases from the Connecticut Tumor Registry. Three neuropathologists independently and blindly reviewed tumor slides from 204 cases and a nosologist blindly reviewed and assigned International Classification of Diseases for Oncology (ICD-O) codes to 326 cases. For the pathology review, absolute concordance was as high as 81% for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…In a recent assessment of patients with brain tumors from the Connecticut Tumor Registry (a SEER site), absolute concordance rates of 49 -81% were observed for the pathology review, with mixed tumors having relatively high discordance rates relative to pathology review. 31 Numerous other retrospective studies have presented survival rates for patients with low-grade gliomas by surgical resection extent (gross total, subtotal, or biopsy); however, they are difficult to compare with the current data, because most of those studies did not present estimates by specific age or histologic groups, and nor did they provide confidence interval estimation for risk estimates. Furthermore, many of the previous studies included subtypes of patients that were not included in the current study, such as patients with diagnoses of epilepsy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a recent assessment of patients with brain tumors from the Connecticut Tumor Registry (a SEER site), absolute concordance rates of 49 -81% were observed for the pathology review, with mixed tumors having relatively high discordance rates relative to pathology review. 31 Numerous other retrospective studies have presented survival rates for patients with low-grade gliomas by surgical resection extent (gross total, subtotal, or biopsy); however, they are difficult to compare with the current data, because most of those studies did not present estimates by specific age or histologic groups, and nor did they provide confidence interval estimation for risk estimates. Furthermore, many of the previous studies included subtypes of patients that were not included in the current study, such as patients with diagnoses of epilepsy.…”
Section: Discussionmentioning
confidence: 85%
“…Eligible study participants for this analysis included all patients who underwent resection within the intraoperative MRI operating suite at BWH in Boston who were diagnosed with a unifocal, histologically confirmed, low-grade (Grade 1 or 2), supratentorial, nonoptic pathway glioma between January 1, 1997 and January 31,2003, and who had a minimum of 1 year of follow-up (n ϭ 156 patients). The histologic subtypes included in this analysis were astrocytoma (International Classification of Diseases for Oncology [ICD-O] codes 9400, 9410, and 9420), mixed glioma (ICD-O code 9382), and oligodendroglioma (ICD-O code 9450).…”
Section: Methodsmentioning
confidence: 99%
“…However, studies examining other cancers have demonstrated an acceptable rate of concordance between a patient's pathology and its coded representation in a cancer registry. 5 Despite these limitations, these data add considerably to our understanding of cerebellar low-grade astrocytoma in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent statistical methods were used to produce a model that best classified biopsies in the training data set. The results showed conclusively that protein patterns could readily distinguish between tumor and nontumor tissues, including mapping to individual tumor grades and comparing favorably to studies of interclass observer variability in pathology and neuropathology (11,12). The full data set of 108 glioma patients was then evaluated, averaged by patient, to identify biomarker patterns that correlate to patient survival trends.…”
Section: Protein Signatures In Gliomasmentioning
confidence: 95%